Cross-Cultural Adaptation and Psychometric Evaluation of the Perceived Ability to Cope With Trauma Scale in Portuguese Patients With Breast Cancer - Lemos, Raquel; Costa, Beatriz; Frasquilho, Diana; Almeida, Sílvia; Sousa, Berta; Oliveira-Maia, Albino J. (Frontiers in Psychology, 2022)
Background: The impact of a cancer diagnosis may be traumatic, depending on the psychological resources used by patients. Appropriate coping strategies are related to better adaptation to the disease, with coping flexibility, corresponding to the ability to replace ineffective coping strategies, demonstrated to be highly related with self‐efficacy to handle trauma. The Perceived Ability to Cope with Trauma (PACT) scale is a self-rated questionnaire that assesses the perceived ability to cope with potentially traumatic events, providing a measure of coping flexibility. The current study aimed at examining the psychometric properties of the PACT Scale in Portuguese patients with breast cancer. Methods: The study included 172 patients recently diagnosed with early breast cancer. Participants completed a Portuguese version of the PACT scale, and instruments of self-efficacy for coping with cancer (Cancer Behavior Inventory-Brief Version – CBI-B), of quality of life (European Organization for Research and Treatment of Cancer Quality of Life Questionnaire Core-30 – QLQ-C30), and of psychological distress (Hospital Anxiety and Depression Scale – HADS) that were used as convergent and divergent measures, thus assessing construct validity. A confirmatory factor analysis (CFA) was performed to test the factor structure of the Portuguese version of PACT scale and reliabilities were examined. Results: Results from the CFA confirmed the two-factor structure, consistent with the original Forward and Trauma focus subscales. The two subscales demonstrated high internal consistencies. Convergent and divergent validities were confirmed: the PACT scale was related to high self-efficacy to cope with cancer (CBI-B), to high perceived quality of life (QLQ-C30), and to low psychological distress (HADS). Discussion: Overall, the current results support and replicate the psychometric properties of the PACT scale. The scale was found to be a valid and reliable self-reported measure to assess Portuguese breast cancer patients regarding beliefs about their capabilities in managing the potentially traumatic sequelae of cancer. The PACT is a simple and brief measure of coping flexibility to trauma, with potential relevance for application in clinical and research settings.